HDLs, immunity, and atherosclerosis - Norata, Giuseppe; Pirillo, A.; Catapano, A. (Lippincott Williams & Wilkins, 2011)
Purpose of Review: HDLs possess several physiological activities that may explain their antiatherosclerotic properties. Among them, the most relevant is the ability of HDL to promote the efflux of excess cholesterol from peripheral tissues to the liver for excretion. Recent Findings: The ability of HDL to promote cholesterol efflux results also in the modulation of a series of responses in the immune cells involved in atherosclerosis, including monocyte-macrophages, B and T lymphocytes. HDL also acts as a reservoir for a number of biologically active substances that may impact the immune system, and as the HDL composition varies to a large extent during inflammation. Summary: The understanding of how these interactions take place and how biologically active substances can be delivered to relevant targets during atherogenesis is of great interest and may provide a better understanding for the role of HDL in atherogenesis. © 2011 Wolters Kl uwer Health | Lippincott Williams & Wilkins.